Forest and Land Fire Danger Mapping Based on Land Physical Parameters in Sumatera and Kalimantan Region of Indonesia - Ardila Yananto; M. Bayu Risky Prayoga; Budi Harsoyo (Politeknik Negeri Batam, 2017)
Indonesia is a country that vulnerable to land and forest fires danger. This is not out of the presence of peatland in Indonesia is quite wide, which are mostly located in Sumatara and Kalimantan. The nature of peatlands are capable to store water in large quantities, but the surface dries quickly and become flammable during the dry season. This research aims to perform mapping areas that vulnerable to land and forest fires danger based on the physical parameters. Based on the results obtained can be used as the basis for develop land and forest fires early warning system in Indonesia. This research use GIS (Geographic Information System) for processing mapping of physical parameters which consists of Land Use Map, Topography Map and Soil Map in Sumatra and Kalimantan to get the forest and land fires danger map. The results of the mapping areas that vulnerable to forest and land fire based on the physical parameters resulting from this study have uniform patterns with the distribution and density of hotspots in the Sumatra and Kalimantan over the last 10 years (2006-2015). This is reinforced by the result of mapping accuracy test, where the percentage number of hotspots during the last 10 years both in Sumatera and Kalimantan area which is exactly vulnerable up to very vulnerable to land and forest fires danger by 74%.